Development and characterization of a novel nanosuspension based drug delivery system of valsartan: A poorly soluble drug (Asian Journal of Pharmaceutics (AJP), 2015)
The purpose of the present study was to formulate valsartan nanosuspension to increase the aqueous solubility and toÂ improve its oral bioavailability. Valsartan is a poorly waterâ€soluble drug which results in its insufficient bioavailability.Â Low oral bioavailability of poorly waterâ€soluble drugs poses a great challenge during drug development. Poorly waterâ€solubleÂ drugs are difficult to develop as drug products, using conventional formulation techniques. Valsartan nanosuspension wasÂ prepared by pearl milling technique using zirconium oxide beads as a milling media and poloxamer 407 (Lutrol F 127) asÂ a stabilizer. Effects of various process parameters like, stirring time and the ratio of the beads were optimized by keepingÂ drug: Surfactant as a constant initially and then optimized process parameters were used to optimize the formulation. TheÂ optimized formulation of nanosuspension was used as granulating fluid as well as spray dried onto the mannitol (PearlitolÂ SD 200) and formulated into tablets. The nanosuspension was characterized by particle size, size distribution analysis, andÂ differential scanning calorimetry. The nanosuspension was evaluated for drug content, drug release by in vitro dissolutionÂ studies and stability.The nanosuspension with 0.3% poloxamer showed improved solubility and dissolution rate.The in vitroÂ dissolution profile of valsartan nanosuspension performed in 6.8 pH phosphate buffer as medium showed complete release.Key words: Nanosusupension, pearl milling, poloxamer, valsartan